THE ROLE OF INNOVATIVE TECHNOLOGIES IN AGRICULTURAL MANAGEMENT - Asadullina Nailya Ramilevna; Normurodov Sarvar Norboy o’g’li (European Science Publishing, 2025)
Investment is one of the necessary conditions for effective and sustainable development of agriculture. This article talks about the ways of attracting investments in agriculture and their effective use and it talks about the construction of innovative projects.
Keywords: Investments and innovations, income and profit, income and depreciation deductions, reconstruction, irrigation, construction of modern facilities.